PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI VEKTOR DI KELAS X.2 SEMESTER II MAN 2 PIDIE JAYA TAHUN PELAJARAN 2021/2022 - Ulfa Nuriza (Pedir Research Institut, 2022)
This study aims to find out and understand the mathematics lesson plan, the ongoing process of learning mathematics, and the abilities and weaknesses of students in Class X.2 MAN 2 Pidie Jaya in vector material after learning using the demonstration method in class X.2 MAN 2 Pidie Jaya. This type of research is Classroom Action Research (CAR). Data collection was carried out by preparing learning tools, implementing actions, observing, and self-reflection. Data analysis is done quantitatively and qualitatively. The results of data analysis showed that the acquisition of student learning outcomes with an average value in the first cycle: 67.64, the second cycle: 81.48. Thus it can be concluded, the application of the demonstration method to vector material can improve student learning outcomes. This can be seen by the large participation of students during the learning process, as well as the interest of students to share experiences and information with their friends. So that all students can understand each material presented either through the researcher's explanation or through the guidance and direction of his friends